PENGEMBANGAN PANDUAN PENULISAN PROPOSAL DAN SKRIPSI MAHASISWA DENGAN PENULISAN BIBLIOGRAFI BERBASIS ENDNOTE PROGRAM DAN MANUAL JURUSAN BAHASA INGGRIS FBS UNM - Sultan Sultan; Mardiyanah Nasta (Seminar Nasional LP2M UNM, 2019)
The study aimed at developing undergraduate student proposal and thesis guidebook using EndNote Program and reference style using APA 6th of English Department of Faculty of Languages and Literature of Universitas Negeri Makassar. The design of the study was Research and Development (R&D). The study adapted Thiagarajan’s Four-D (Define, Design, Develop, dan Disseminate) Research and Development (R&D) model because this model is suitable with subject characteristics, student psychological development, and the variety of the student’s mother tongue. The participants of the study were the sixth semester students of English Literature Study Program of FBS UNM who joined “Research Method in Language and Literature” subject in 2018/2019 academic year and “Seminar of English Language and Literature” 2019/2020 academic year. Multiple trials were employed to find the final prototype. The results of the study showed: (1) the participants agreed EndNote Program Module and Referencing Guide Book are beneficial for them; (2) EndNote Program Module and Referencing Guide Book which are developed are relevant with the subject their programmed; and (3) Most of the students (more than 90%) believed that the guidebook which had been designed was very helpful in writing research proposal and result. The outputs of this study were: (1) Guide Book of how to write proposal guidebook and how to write bibliography (references) using APA 6th style; (2) Article which had been presented in the National Seminar of LP2M of UNM on November 16, 2019 in Makassar.